E-EVALUATION: HOW TO BUILD AN EASY AND PAPERLESS EVALUATION SYSTEM WITH LIMITED RESOURCES (CASE STUDY AT EDUCATION AND TRAINING CENTER FOR BSSN) - Setyowati, Anik; Ma’ruf, Kholif Faiz (PEOPLE: International Journal of Social Sciences, 2018)
Evaluation as an important component in the implementation of a training should be done not only to measure the success of a training program but also as input and suggestion for the development of future training program. The usual method of training evaluation is to use paper that certainly cost and time, not to mention the process of data input and compilation. When the method is changed using softcopy that is sent via email, the constraint still continues. Not to mention when not all users have personal email. Development using online application tools would require a large resource, while in Education and Training Center of BSSN have limited resources both human resources and funds. However, this should be done for the success of paperless and e-Government programs in the government institutions carried by BSSN.The author tries to make the evaluation design by using the available online tools, google forms, with elements of assessment that have been determined in the rules. This form link will be dispersed through whatsapp application facility to each of the users from one of the training programs as the case study.From the results of the distribution of the link obtained the e-evaluation design results not only facilitate the user but also able to save costs and time, facilitate the process of data input and compilation and control functions to the process of collecting the form again, especially for users from outside Education and Training Center of BSSN environment.